Case Report: Deep brain stimulation improves tremor in FGF-14 associated spinocerebellar ataxia - Loeffler, Moritz A.; Synofzik, Matthis; Cebi, Idil; Klocke, Philipp; Hormozi, Mohammad; Gasser, Thomas; Gharabaghi, Alireza; Weiss, Daniel (Frontiers in Neurology, 2022)
Objectives Spinocerebellar ataxia 27 (SCA 27) is a rare heredodegenerative disorder caused by mutations in the fibroblast growth factor 14 (FGF14) and characterized by early-onset tremor and progressive ataxia later during the disease course. We investigated the effect of deep brain stimulation (DBS) of the ventralis intermedius nucleus of the thalamus (VIM) and subthalamic projections on tremor and ataxia. Methods At baseline, we studied the effects of high-frequency VIM stimulation and low-frequency stimulation of subthalamic projections on tremor and ataxia. The patient then adopted the best individual high-frequency stimulation programme at daytime and either 30 Hz-stimulation of the subthalamic contacts or StimOFF at night during two separate 5-weeks follow-up intervals. Both patient and rater were blinded to the stimulation settings. Results High-frequency stimulation of the VIM effectively attenuated tremor. At follow-up, intermittent 30 Hz-stimulation at night resulted in a superior tremor response compared to StimOFF at night. Ataxia was not affected. Discussion Stimulation of the VIM and adjacent subthalamic projections effectively attenuated tremor in a patient with confirmed SCA 27. Cycling between daytime high-frequency and night-time low-frequency stimulation led to a more sustained tremor response. This suggests to study in future if low-frequency stimulation of the subthalamic projection fibers may help overcome tolerance of tremor that is observed as a long-term limitation of VIM-DBS.